Towards an Effective Regime of the Application of Condonation, Compounding of Offences and Plea Bargaining as Veritable Alternative Dispute Resolution (ADR) Mechanisms - Saheed, Abiola Adekunle (ABUAD Law Journal, 2023)
The recent court queues, rising costs of litigation, congestion in prisons, expensive nature of management of prisons and time delays has continued to affect the administration of criminal justice system in Nigeria. There is therefore the need to fashion out alternatives to administration of criminal justice. These alternatives if effectively used in the administration of criminal justice system, it will not only reduce the congested nature of our prisons but also reduce the workload of the courts. It is against this backdrop that this paper seeks to examine the effective regime of the application of Condonation, Compounding of offences and Plea bargaining as veritable Alternative Dispute Resolution (ADR) Mechanisms. This paper adopted historical and analytical approaches through the use of primary and secondary documents as contained in published and unpublished materials. The paper revealed that compounding of offences even though it predated plea bargain, Nigeria has not yet made clear and general provisions on compounding of offences under the Penal Laws. The paper concluded that compounding of offences, condonation and plea bargaining are veritable alternative dispute resolution mechanisms embedded in the administration of criminal justice system. It was recommended among others that a uniform and generally applicable law should be enacted on condonation, compounding of offences and Plea bargaining in Nigeria, harmonization of our substantive criminal laws and procedural Criminal Codes in Nigeria and a more suitable sentencing guidelines for plea bargaining.